Fabrication of ZnO/Si lamb wave acoustic devices. (26th October 2018) - Rana, Lokesh; Gupta, Reema; Sharma, Anjali; Tomar, Monika; Gupta, Vinay
Abstract: Surface acoustic wave devices have widespread applications in various fields including in communication and wireless sensing devices. However some shortcomings like lower sensitivity and the corrosion of IDT's limit their application as sensing devices. Lamb wave SAW devices have proved to be promising for sensing applications. In the present work effort has been made to find out the optimum etching temperature in order to get the sufficiently fast etch rate and smooth surface for the fabrication of SiO2 /Si membrane for Lamb wave acoustic (LWA) devices. Piezoelectric ZnO thin film deposited using rf sputtering technique has been integrated with the SiO2 /Si membrane. The bulk etching of Silicon has been carried out from back side of each LWA device using wet etching. The devices are packaged and frequency response is studied using a network analyzer. The antisymmetric and symmetric modes of the Lamb wave devices have been identified.